Ecologia de pequenos mamíferos (Didelphimorphia e Rodentia) em uma área de caatinga do Rio Grande do Norte - Pereira, Viviane Morlanes (2016)
The Caatinga biome occurs in the states of the states of Maranhão, Piauí, Ceará, Rio Grande do Norte, Pernambuco, Paraíba, Alagoas, Sergipe, Bahia and Minas Gerais, in Brazil. Despite being the only exclusively Brazilian ecosystem, few resources for research on biodiversity and conservation are devoted to this biome. The generation of knowledge on biodiversity of the Caatinga is essential for establishing effective strategies for management and conservation of species and habitats, particularly in a biome as sensitive and as threatened this one. The present work is divided into two chapters. The first one is an extensive literature review on the occurrence, distribution and chromosomal characteristics of species of small terrestrial mammals recorded in the Caatinga. The second chapter presents data on diversity, ecology and seasonality of a community of small terrestrial mammals (Didelphimorphia and Rodentia) using capture-marking-recapture methods throughout twelve successive months in a well-preserved native forest fragment of Caatinga located at the Experimental Farm Rafael Fernandes from the Universidade Federal Rural do Semi-Árido, Mossoró-RN